ESC 2019 guidelines on chronic coronary syndromes: can calcium scoring improve the risk underestimation associated with the updated pre-test probability risk score?. (8th February 2021) - Fyyaz, S; Rasoul, H; Olabintan, O; David, S; Plein, S; Alfakih, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The European Society of Cardiology (ESC) published an updated stable chest pain guideline in 2019. It recommends the use of an updated pre-test probability (PTP) risk score (RS) to assess the likelihood of coronary artery disease (CAD), to try and reduce the risk overestimation associated with previous risk scores. We sought to assess the performance of the 2019 PTPRS in a contemporary cohort of patients undergoing CT coronary angiography (CTCA). Furthermore, we focussed on patients with PTPRS <15%, and assessed the utility of CT calcium scores as a discriminator of risk. Methods: 652 patients who were investigated with CTCA for stable chest pain between January 2017 and May 2018 were included in a retrospective analysis. CTCA reported CAD degree of stenosis as normal/minimal stenosis, mild (30-50%), moderate (50-70%), or severe (>70%). ESC 2019 pre-test probability risk scores were retrospectively calculated and compared. Results: A total of 652 patients underwent CTCA between 01 January 2017 and 31 May 2018, of which 330 were male and 322 were female, with an average age of 55 years ±11 years. Using the ESC 2019 PTPRS there were no patients with PTPRS >85%. 2 patients had PTPRS 50-85%; one patient had moderate stenosis and one mild stenosis on CTCA.  There were 267 patients with PTPRS 15-50%; 23 (9%) patients had severe CTCA stenosis, 37 (14%) a moderate stenosis, and 34 (13%) a mild stenosis. A further 379 patients had PTPRS <15%; 11 (3%) had severe stenosis and 20 (5%) moderate stenosis. A further 27 (7%) patients had mild CTCA stenosis.  A total of 357 of 379 patients with PTPRS <15% based on ESC 2019 had a CT calcium score. 236 patients were found to have a calcium score of zero, and 121 patients had a score greater than zero, with a range between 1 and 930. Of patients with zero calcium score, only 1 (0.4%) patient had severe stenosis, 2 (0.8%) moderate stenoses and 6 (2.5%) mild stenosis. In contrast, in patients with positive calcium scores, 10 (8%) had severe stenosis, 18 (15%) moderate stenosis, and 22 (18%) mild stenosis. Conclusions: The ESC 2019 PTPRS classified this as an overall low risk cohort. The downward risk modification of PTPRS has led to a large number of patients being classified as low risk with PTPRS <15%. No or deferred investigation is recommended by the ESC in this cohort. However, the use of CT calcium scores  in patients with PTPRS <15%, detected the majority of patients with any degree of CAD. CT calcium scores are a simple and low cost risk modifier, and may help identify patients who may benefit from primary prevention as per SCOT-Heart. Patients with calcium score greater than zero could be investigated with CTCA.